Aggregate and Disaggregate Natural Resources Agglomeration and Foreign Direct Investment in France - Audi, Marc; Ali, Amjad; Roussel, Yannick (International Journal of Economics and Financial Issues, 2021)
The inflow of foreign direct investment shows the economic and political strength of a country (Bevan & Estrin, 2004). Resources agglomeration and foreign direct investment have a theoretical and empirical relationship (Carlton, 1983; Hansen, 1987; Krugman, 1991; Wheeler and Mody, 1992; Friedman et al., 1992; Head et al., 1995; Henderson and Kuncoro, 1996; Head and Ries, 1996; Devereux and Griffith, 1998; Head et al., 1999; Guimaraes et al., 2000). This paper has examined the impact of aggregate and disaggregates natural resources agglomeration on foreign direct investment in the case of France from 1989 to 2012. Seven different model specifications are used for empirical analysis. The inflow of foreign direct investment from Greece, Australia, Austria, Germany, Canada, Finland, Ireland, Hungary, Israel, Japan, Italy, Republic of South Korea, Switzerland, Norway, Netherlands, Poland, Spain, Portugal, Sweden, Turkey, United States, Mexico, Korea and United Kingdom in France is taken as the dependent variable. Total natural resources agglomeration, population density, trade openness, secondary education, taxes, inflation rate, primary education, agriculture land agglomeration, forest agglomeration, oil production agglomeration, mineral production agglomeration and natural gas production agglomeration are selected as explanatory variables. The results show that aggregate and disaggregate natural resources agglomeration are important indicators of foreign direct investment. The results show that the population density is a key indicator of foreign direct investment, the current population growth of France and many developed countries is below the replacement rate. Agriculture land agglomeration, oil production agglomeration and mineral production agglomeration are the inputs of many economic activities. This shows that for higher amount of foreign direct investment, natural resources agglomeration must be encouraged. Keywords: natural resources agglomeration, foreign direct investment JEL Classifications: N5, F21 DOI: https://doi.org/10.32479/ijefi.10869